Oribatid mites (Acari, Oribatida) of Saona Island, Dominican Republic - Sergey G. Ermilov (Persian Journal of Acarology)
Thirty-four species of oribatid mites (Oribatida), belonging to 29 genera and 14 families, were collected from Saona Island, Southeast Dominican Republic. A new species of the genus Pergalumna—P. (Pergalumna) saonaensis sp. nov.—is described from leaf litter of the mixed forest.